Telehealth and technological applications in patient‐centered care: Implications for pharmacy learners and clinical pharmacists. Issue 8 (20th July 2021) - Badowski, Melissa E.; Bente, Jessica A.; Davis, Estella M.; Isaacs, Diana; Lewis, Lindi; Martello, Jay L.; Pitlick, Matthew; Almodóvar, Armando Silva; Stadler, Sheila; Sutton Burke, Elizabeth; Belk, Madeline; Tovey, Amber; et al.
Abstract: Telehealth has emerged as an essential health care delivery modality to improve patient access to health care and allow providers to meet their patients' health care needs. It is imperative that pharmacy learners and clinical pharmacists have the requisite knowledge and skills to comfortably deliver patient‐centered care via telehealth with devices, software, digital therapeutics, wearables, and other technological applications. This manuscript supplements the existing ACCP resources on this subject, educates clinical pharmacists on the rapidly advancing field of telehealth and its available technologies, and summarizes methods for training current and prospective clinical practitioners.